Anionic polymerization of p-(2, 2′-diphenylethyl)styrene and applications to graft copolymers. Issue 1 (1st January 2017) - Huang, Minglu; Han, Bingyong; Lu, Jianmin; Yang, Wantai; Fu, Zhifeng
Abstract: Well-controlled anionic polymerization of an initiator-functionalized monomer, p -(2, 2′-diphenylethyl)styrene (DPES), was achieved for the first time. The polymerization was performed in a mixed solvent of cyclohexane and tetrahydrofuran (THF) at 40 °C with n -BuLi as initiator. When the volume ratio of cyclohexane to THF was 20, the anionic polymerization of DPES showed living polymerization characteristics, and well-defined block copolymer PDPES- b -PS was successfully synthesized. Furthermore, radical polymerization of methyl methacrylate in the presence of PDPES effectively afforded a graft copolymer composed of a polystyrene backbone and poly(methyl methacrylate) branches. The designation of analogous monomers and polymers was of great significance to synthesize a variety of sophisticated copolymer and functionalize polymer materials.